Effects of a positive psychological intervention on psychological states and functional brain imaging of nurses in transition training: a quasi-experimental study - He, Li; Wang, Haiyan; Guo, Zhiwei; Zhou, Yu; Hu, Lu; Zhao, Juan; Chen, Yi; Xiang, Li (Frontiers in Human Neuroscience, 2025)
ObjectiveTo explore the effects of a positive psychological intervention on the psychological state and brain function of trained nurses during the transition period.MethodsRandomization was used to assign 130 trained nurses to the observation and control groups. The control group underwent routine training, while the observation group underwent a 12-week positive psychological intervention based on the “Three Good Things” program. The Core Self-Evaluation Scale, Patient Health Questionnaire Depressive Symptom Cluster Scale, Generalized Anxiety Disorder Scale, and resting-state functional magnetic resonance imaging were used for data collection pre- and post-intervention. The amplitude of low-frequency fluctuation, fractional amplitude of low-frequency fluctuation, and regional heterogeneity indices were calculated to assess the functional brain activity of the participants. Pearson’s correlation coefficient was used to assess the relationship between the changes in brain function and behavior.ResultsThere was no difference in the general information of the two groups pre-intervention. Post-intervention, the observation group reported higher self-evaluation scores and lower anxiety and depression scores than the control group. The amplitudes of low-frequency fluctuation of the observation group were significantly higher than those of the control group in the bilateral calcarine gyrus, left cuneus lobe, left supramarginal gyrus, left middle temporal gyrus, left inferior frontal gyrus, left inferior parietal lobe, right superior parietal lobe, right angular gyrus, and right middle temporal gyrus. The observation group displayed significantly higher regional heterogeneity values in the bilateral superior parietal lobe, bilateral supramarginal gyrus, and bilateral inferior parietal lobe (p < 0.05).ConclusionPositive psychological interventions based on the “Three Good Things” program can assist nurses in training during the transition period to enhance their core self-assessment ability, alleviate their anxiety and depression, and improve their sense of occupational identity and mental health.